Spermatic cord block in open inguinal hernioplasty - Roy, Arijit; Bhar, Anindita; Das, Tamoghna (International Journal of Clinical Trials, 2022)
Background: Spermatic cord block is a useful technique for providing anesthesia with scrotal pain and it has been described and published in the urology and anesthesia literature for more than 40 years. Spermatic cord block for inguinal hernioplasty along with spinal anaesthesia avoids the potential risks of neuraxial and general anesthesia and provides long-lasting postoperative analgesia. The aim of this study is to evaluate the postoperative effect of 0.5% Bupivacaine for spermatic cord block along with spinal anaesthesia in inguinal hernioplasty. Methods: This study was carried out in KPC medical college and hospital on 100 patients with ASA physical status I and II, age older than or equal to 18 years undergoing elective open inguinal hernioplasty from September 2021 to August 2022. Patients were randomly allocated into two equal groups: 50 patients received spermatic cord block after mesh placement by bupivacaine 5 ml (0.5%), and 1 ml normal saline (group 1), and 50 patients received 6 ml saline injection in spermatic cord. Results: There was no significant difference between the demographic data, patient characteristics, heart rate, mean arterial blood pressure, and oxygen saturation in the studied groups. There was significantly rapid onset and prolonged duration of blockade, significant decrease in visual analog scale score at 6 h and 12 h postoperatively and the amount of rescue analgesia in group 1 respectively. Conclusions: Spermatic cord block in inguinal hernioplasty surgery improves onset of the block, prolongs postoperative analgesia and reduces the consumption of of postoperative rescue analgesics.